Triumphal entrance of 8th count of Oñate in Naples: an allegorical drawing of a lost portrait by Jusepe de Ribera - Minguito Palomares, Ana (Cuadernos de Historia Moderna, 2015)
In this paper we identify and analyze an anonymous drawing that has turned up in the Museo del Prado´s collection. This drawing depicts the triumphant entrance into Naples of the 8th Count of Oñate Íñigo Vélez de Guevara y Tassis. We account for its characteristics as an example of an image used to consolidate power in the 17th century. We propose that the equestrian portrait of the count of Oñate, which dominates the scene, is a copy of a lost portrait by Jusepe Ribera. We attribute the authorship of the drawing to Nicolas Perrey, who completes the picture with an allegorical-symbolic recreation of the virtues of the ruler being acclaimed. The drawing recreates the ceremony organized for the opening of Palazzo degli Studi after the Masaniello riots. This ceremony, explained in the publication Theatrum Omnium Scientiarum, was celebrated with clear propaganda intentions in order to restore social order in Naples and strengthen the Spanish power in the kingdom.
Keywords: Naples; Masaniello; count of Oñate; Jusepe Ribera; Nicolas Perrey; triumphal entrance; Theatrum Omnium.